The Effects of Moderate Intensity Treadmill Exercise with Gradual Increase of Speed and Inclination on VO2max in Men with Type 2 Diabetes Mellitus - Mas'adah Mas'adah; Damayanti Tinduh; Nur Sulastri; Sony Wibisono Mudjanarko (Surabaya Physical Medicine and Rehabilitation Journal, 2021)
Background: The American College of Sport Medicine (ACSM) recommends cardiorespiratory fitness training in people with diabetes mellitus (DM) for 3-7 days a week, total duration 150 minutes a week with moderate intensity using large muscle groups. Treadmill training is the best cardiorespiratory fitness training because it involves large muscle group compared to static cycle and arm crank.Aim: To determine the effect of moderate intensity treadmill exercise with gradual increase of speed and inclination on VO2max in men with T2DM.Material and Methods: Randomized group design in 22 men with T2DM, suitable with inclusion criteria was divided into 2 groups, the experimental and control group. The experimental group received moderate intensity treadmill exercise, 3 times a week with gradual increase of speed and inclination for 4 weeks. The control group underwent standard therapy. Measurement of VO2max was performed before and after program in both groups.Results: A significant increase of VO2max in the experimental group (p = 0.003). Compared to the control group, alteration of VO2max also significant among the experimental group (p = 0.000).Conclusion: Moderate intensity treadmill exercise with gradual increase on speed and inclination for 4 weeks increase VO2max in men with T2DM.